O-232 Higher clinical pregnancy rate after oxytocin-receptor antagonist administration around the time of embryo transfer: A systematic review and meta-analysis of eleven RCTs. (6th August 2021) - Neumann, K; Griesinger, G
Abstract: Study question: Does the administration of an oxytocin-receptor antagonist around time of embryo transfer in IVF impact the likelihood to achieve a clinical pregnancy? Summary answer: Administration of oxytocin-receptor antagonists around embryo transfer increases the likelihood of clinical pregnancy achievement. What is known already: Uterine contractions occurring around time of embryo transfer have been described as one possible mechanism of failure of implantation of an embryo in the context of in-vitro fertilization (IVF). Hence the utilization of oxytocin-receptor antagonists was evaluated in randomized clinical trials (RCT) as a therapeutic approach. The compound Atosiban was studied by most RCTs (summarized in Huang et al. 2017). Recently further studies have become available which also investigated the novel agents Barusiban and Nolasiban. This systematic review collates the evidence of all drugs functioning as oxytocin-receptor antagonists which have been investigated in RCTs on IVF treatment so far. Study design, size, duration: Multiple literature databases were searched for randomized controlled studies comparing the outcome of IVF cycles with administration of an oxytocin-receptor antagonist in the time period before, during or after embryo transfer versus placebo or nil in IVF patients. Meta-analyses were performed using standard procedures in the software program RevMan v.5.4. All analyses were done per randomized patient, wherever feasible. Participants/materials, setting, methods: Eleven RCTs were identified and included in the meta-analysis. Seven utilized the agent Atosiban, one Barusiban and three Nolasiban. These drugs were administered either intravenously, subcutaneously or orally. The patient populations were heterogenous (fresh cycle, frozen-thawed cycle, endometriosis, implantation failure or general IVF-population) between trials. Only four studies reported live birth rates whereas all RCTs reported clinical pregnancy rate. Main results and the role of chance: Administration of an oxytocin-receptor antagonist around embryo transfer increases the likelihood of live birth (relative risk: 1.1, 95% CI: 0.99-1.22, p = 0.06, I 2 =31%, four RCTs, n = 2, 510). Accordingly, the ongoing pregnancy rate is increased (relative risk: 1.14, 95% CI: 1.03-1.26, p = 0.01, I 2 =18%, four RCTs, n = 2, 510) as well as the clinical pregnancy rate (relative risk: 1.31, 95% CI: 1.13-1.51, p = 0.0002, I 2 =61%, eleven RCTs, n = 3, 611) by administration of an oxytocin-receptor antagonist. The risk to suffer a miscarriage, however, is not influenced by an oxytocin-receptor antagonist administration (relative risk: 0.90, 95% CI: 0.72-1.12, p = 0.35, I 2 =0%, seven RCTs, n = 2, 936). The risk of multiple pregnancy is not different between groups (relative risk: 1.05 95% CI: 0.81-1.36, p = 0.73, I 2 =5%, seven RCTs, n = 3, 014) as is the risk for an ectopic pregnancy (relative risk: 0.88 95% CI: 0.43-1.8, p = 0.73, I 2 =0%, four RCTs, n = 2, 714). Limitations, reasons for caution: Methodological rigor is heterogenous between trials and some of the evidence is of poor quality. Evaluation of included studies is still ongoing and queries are pending. Additionally, there is heterogeneity between patient populations and definition of outcomes; only four RCTs report ongoing pregnancies and live births. Wider implications of the findings: The administration of oxytocin-receptor antagonists around embryo transfer increases the pregnancy rate and may be a promising approach to enhance the likelihood to achieve a live birth per embryo transfer. Trial registration number: n.a.